A novel transceiver structure including power and audio amplifiers for Internet of Things applications. (August 2017) - Ghorbani, A.R.; Ghaznavi-Ghoushchi, M.B.
Abstract: Both of the Circuit and System design aspects of the Internet of Things (IoT) are emerging with computation and communication issues. In communication, it utilizes transceivers like wireless sensor network (WSN). In spite of the conventional WSN, a key component of IoT is its direct engagement with humans (animals). Therefore, communication is required in audio–visual ranges. This means an IoT device (IoTD) will be ported with audio amplifiers. This paper presents a novel IoT transceiver with a reconfigurable PA-CDA with time-domain and task-oriented multiplexing. The run-time reconfiguration of an area-power-efficient common part is utilized. The topology and scheduling issues of the Bluetooth Low Energy (BLE) standard are well-suited to the proposed architecture. Time, energy, and protocol concerns are studied and appropriate models presented. The PA and CDA operate in the 2.4 GHz and audio-range frequencies, respectively. The battery life and power consumption are improved by about 40% and 20%, respectively.